Teachers' Efforts in Overcoming Social Control-Based Student Indiscipline in Madrasahs - Sukma Elga Safrianti (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to explore teachers' efforts in overcoming social control-based student indiscipline at Madrasah School. Using a qualitative approach with a case study method, this research collected data through in-depth interviews with teachers, students, and principals. Social control theory was used as an analytical framework to explore how norms and rules in madrasahs influence students' behavior. The results showed that teachers at Madrasah Darussalam use a combination of formal and informal approaches in managing students' behavior, emphasizing on religious and social values as the basis of social control. This research is expected to contribute to the development of more effective discipline management strategies in the madrasah environment.